PEMBINAAN PEDAGANG KANTIN SEKOLAH TERHADAP PERUBAHAN SANITASI, TOTAL MIKROBA, SERTA ESCHERICHIA COLI - Maghfiroh, Rahmi Naily; Nurrahman, Nurrahman; Suyanto, Agus (Nindikayla Institute, 2023)
The sanitary condition of the canteen has an impact on food safety and the health of school residents. Foodstuffs contaminated with microorganisms cause unwanted damage and are therefore unfit for consumption. This study aims to determine the role of coaching school canteens on changes in sanitation levels, total microbes, and Escherichia coli. Counseling on food safety was given to the five canteen traders. Then training was carried out for thirty days with nine meetings. During the training, the canteen traders were given instructions regarding safe food processing and facilities to support hygiene and sanitation in the canteen. In order to determine the success rate of coaching, tests on the level of sanitation, total microbes, and Escherichia coli contamination in food and water sources were carried out before and after the coaching activities. The score of the five canteen sanitation level questionnaires increased after coaching. There was a change in the total microbes in the food samples but not significantly. Total microbes of water samples experienced a significant decrease in the four canteens, while one canteen did not change. Escherichia coli contamination test results decreased in the three canteens, while the two canteens experienced an increase. Coaching has an influence on the level of sanitation, decreased total microbes, and Escherichia coli contamination.